2015
DOI: 10.1007/s00586-015-4073-0
|View full text |Cite
|
Sign up to set email alerts
|

Burden of disease of reoperations in instrumental spinal surgeries in Germany

Abstract: Costs of ISS and subsequent reoperations have a significant impact on health insurances budgets. The annual cost of reoperations exceeds the direct cost of the primary surgery driven by the need for further inpatient and outpatient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(33 reference statements)
0
1
1
Order By: Relevance
“…Lumbar fusion surgery is a standard procedure for treating degenerative lumbar disease. Despite advances in surgical technique and implants over the past two decades, the rate of unplanned reoperation did not decrease with the increase in lumbar fusion volume [2,6,13]. In the present study, we found that the cumulative incidence of unplanned reoperation was about 4.1% at 3 months, 6.2% at 1 year and 8.2% at 3 years.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Lumbar fusion surgery is a standard procedure for treating degenerative lumbar disease. Despite advances in surgical technique and implants over the past two decades, the rate of unplanned reoperation did not decrease with the increase in lumbar fusion volume [2,6,13]. In the present study, we found that the cumulative incidence of unplanned reoperation was about 4.1% at 3 months, 6.2% at 1 year and 8.2% at 3 years.…”
Section: Discussioncontrasting
confidence: 63%
“…Unplanned reoperations after lumbar fusion are defined as any indications resulting in an unplanned return to the operating room. Previous studies demonstrated the associations between reoperation and worse outcomes, including higher rates of complications and lower satisfaction [6,7]. In a retrospective cohort study of 5022 patients, Weir et al [8] found that mean costs in the 2 years following reoperation were £1889 higher than patients who did not undergo repeat surgery over an equivalent follow-up period.…”
Section: Introductionmentioning
confidence: 99%